Liquid vibrations in cylindrical tanks with and without baffles under lateral and longitudinal excitations - Strelnikova, Elena; Kriutchenko, Denys; Gnitko, Vasyl; Tonkonozhenko, Anatoly (Zielona Góra: Uniwersytet Zielonogórski)
The paper is devoted to issues of estimating free surface elevations in rigid cylindrical fluid-filled tanks under external loadings. The possibility of baffles installation is provided. The liquid vibrations caused by lateral and longitudinal harmonic loadings are under consideration. Free, forced and parametrical vibrations are examined. Modes of the free liquid vibrations are considered as basic functions for the analysis of forced and parametric vibrations.
Keywords: sloshing; cylindrical tank; baffle; free and forced vibrations; parametric resonance; boundaryelement method; Ince-Strutt diagram